Donors after circulatory death pancreas transplantation - Mittal, S; Gilbert, J; Friend, P (Lippincott, Williams and Wilkins, 2017)
The use of organs from donors after circulatory death (DCD) has become standard practice in solid organ transplantation of most abdominal organs and has been used successfully in some centres for pancreas transplantation. Nevertheless, concerns regarding poor graft outcomes and complications remain. This review aims to discuss the current state of DCD pancreas transplantation and the associated outcomes.In many countries, whereas the number of donors after brainstem death (DBD) remains stable, the mean age and BMI have increased making these donors, previously considered to be low risk, now more marginal. Recent meta-analyses have confirmed previous single-centre and registry reports that graft and patient survival after DCD pancreas transplantation are comparable with outcomes using pancreases from DBD donors; DCD pancreas transplantation is now common practice in several countries in Europe, particularly the United Kingdom. Although there have been reports of higher thrombosis rates after DCD pancreas transplantation, the significance of this is difficult to judge as the impact has not been seen in overall graft survival.Pancreas transplantation using DCD organs is well tolerated and feasible when other risk factors are minimized. Although there has been some evidence of an increased risk of thrombosis, this has not translated into a significant difference in graft survival.